ANALISIS LIKUIFAKSI BERDASARKAN DATA SPT DAN PARAMETER FISIK TANAH DI KAWASAN SIBANGGOR TOGA MANDAILING NATAL - Marco Samuel Pangihutan Panggabean; Tika Ermita Wulandari (Fakultas Teknik Universitas Pasifik Morotai, 2025)
Sibanggor Toga in Mandailing Natal is one of the regions characterized by soil properties and geological conditions that are susceptible to liquefaction. Its location within an active seismic zone further highlights the urgency of studies related to this hazard. However, comprehensive investigations utilizing field data, such as Standard Penetration Test (SPT) results, remain very limited for this area. This study focuses on evaluating the liquefaction potential in Sibanggor Toga based on the available SPT data. A quantitative descriptive method was employed, combining liquefaction potential analysis using field data from SPT results and soil physical parameters. The data used in this study consist of SPT field test results (N-SPT values), soil layer depths, fines content (FC), seismicity maps, peak ground acceleration (αmax) obtained from the 2021 Indonesian Design Response Spectrum Application, and relevant literature on soil parameters. The analysis results indicate that the calculated safety factor (FS) values for various soil depths (z) under earthquake magnitudes of 5–7.5 SR are all greater than 1, suggesting that liquefaction is unlikely to occur in the analyzed soil layers. Nevertheless, it is observed that the FS values tend to decrease as earthquake magnitude increases, indicating that dynamic loads have a more significant impact on soil stability. Despite this, structural planning in the area should still consider the soil layers at depths of 4–10 m, as these layers exhibit relatively lower FS values.